Participatory Principles in Forming the Regional Parking Regulations in Makassar City - Nur Azizah; Marwati Riza; Muh. Hasrul (Al-Risalah, 2022)
Considering the importance of community participation in the process of forming local regulations, which are sometimes overlooked by the local government and the Regional House of Representatives, this study was conducted to analyze the forms and implications of community participation in forming the regional parking regulations in Makassar City using an empirical research type. The approaches in this study were the statutory approach, the stratification approach, and the sociological approach. The data analysis used a qualitative method in the form of descriptive analysis. The results of the study showed: 1) the forms of community participation in forming the regional regulations in Makassar City could be divided into three stages. First, community participation in the ante-legislative stage included 1) Research; 2) Discussions, Workshops, and Seminars; 3) Initiative proposals; and 4) Draft Bill. Second, public participation in the legislative stage included 1) Audience; 2) Alternative Draft Bills; 3) input through print media; 4) input via electronic media; 5) demonstrations; and 6) discussions, workshops, and seminars. Third, people's participation in the post-legislative stage included 1) demonstrations, 2) law review, and 3) socialization of the law. The implications for forming regional regulations that do not use participatory principles can be seen from two sides, namely public legal awareness and community legal compliance. The community and parking attendants are aware but disobedient due to several factors, namely accessibility, legal knowledge, understanding of the law, patterns of legal behavior, and factors of the long-standing legal culture of the community. As a result, the effectiveness of forming regional regulations has not been effective because they still need to fulfill the principles of forming laws, namely the principles of efficiency and effectiveness, as well as the principle of openness.